Combination of automated solid-phase and enzymatic oligosaccharide synthesis provides access to α(2, 3)-sialylated glycans. Issue 28 (10th March 2015) - Fair, Richard J.; Hahm, Heung Sik; Seeberger, Peter H.
Abstract : A synthetic strategy combining automated solid-phase chemical synthesis and enzymatic sialylation was developed to access α(2, 3)-sialylated glycans. Abstract : A synthetic strategy combining automated solid-phase chemical synthesis and enzymatic sialylation was developed to access α(2, 3)-sialylated glycans.